Standardizing the Definition of Each Colon Cancer Segment: Delphi Consensus on Clinical Decision-Making for Oncologic Outcomes - Kuzu, Mehmet Ayhan; Benlice, Cigdem; Parvaiz, Amjad; Gorgun, Emre; Bertelsen, Claus A; Wexner, Steven; Dozois, Eric J; Hohenberger, Werner; Miskovic, Danilo; Sugihara, Konichi; Spinelli, Antonino; Wiggers, Theo; et al. (Diseases of the colon & rectum, 2025)
BACKGROUND: Data registries lack a definitive classification system that distinguishes different locations of colon cancer from one another. OBJECTIVE: To establish an international consensus on the definition of primary colon cancer segment locations. DESIGN: Between December 2022 and June 2023, the Delphi survey study was conducted to seek opinions from relevant international experts and eventually develop a consensus definition of each colon cancer segment. SETTING: Three-round online-based Delphi survey study. INTERVENTIONS: The online survey included 17 questions. In the first 2 rounds, participating experts were asked to rank each statement on a scale of 1 (least relevant) to 9 (most relevant). Consensus statements and definitions were revised according to the results for statements obtaining a consensus score of 7 to 9. During the third round and online meeting, definitions and statements that reached a moderate or high consensus (above 4 for more than 70% of participants) were included. MAIN OUTCOME MEASURES: The primary goal of our project was focused on precisely localizing the specific segment affected by primary colon cancer rather than identifying surgical treatment or type of resection needed for a particular segment. RESULTS: The first round included 331 experts; 301 (91%) completed the second round and 295 (98%) completed the final round. Experts strongly supported the use of a "10-cm rule" to describe colon cancer sites at the flexures and anatomical landmarks for other segments. Regarding the definition of rectosigmoid cancer, experts from United States and Europe reached a high consensus that the term rectosigmoid as a colon cancer location must be abolished in contrast to experts from Asia. The description of overlapping segments of cancers achieved a consensus of 64%. LIMITATIONS: Subjective decisions are based on individual expert clinical experience. CONCLUSIONS: This Delphi survey, the first internationally conducted consensus study, achieved a remarkable level of consensus among a panel of global experts. Ambiguity still exists regarding overlapping lesions. See Video Abstract . ESTANDARIZACIN DE LA DEFINICIN DE CADA SEGMENTO DE CNCER DE COLON CONSENSO DELPHI SOBRE LA TOMA DE DECISIONES CLNICAS PARA RESULTADOS ONCOLGICOS: ANTECEDENTES:Las bases de datos carecen de un sistema de clasificación definitivo que distinga las diferentes localizaciones del cáncer de colon.OBJETIVO:Establecer un consenso internacional sobre la definición de las localizaciones de los segmentos del cáncer de colon priamrio.DISEÑO:Entre diciembre de 2022 y junio de 2023, se realizó un estudio Delphi para recabar la opinión de expertos internacionales relevantes y, finalmente, desarrollar una definición consensuada de cada segmento del cáncer de colon.ESCENARIO:Estudio Delphi en línea de 3 rondas.INTERVENCIONES:La encuesta en línea incluyó 17 preguntas. En las dos primeras rondas, se pidió a los expertos participantes que calificaran cada afirmación en una escala del 1 al 9 (9 es la más relevante). Las afirmaciones y definiciones de consenso se revisaron según los resultados, obteniendo una puntuación de consenso de 7 a 9. Durante la tercera ronda y la reunión en línea, se incluyeron las definiciones y afirmaciones que alcanzaron un consenso moderado o alto (superior a 4 en más del 70 % de los participantes).MEDIDA PRINCIPALES DE RESULTADOS:El objetivo principal de nuestro proyecto se centró en localizar con precisión el segmento específico afectado por el cáncer de colon primario, en lugar de identificar el tratamiento quirúrgico o el tipo de resección necesario para un segmento en particular.RESULTADOS:La primera ronda incluyó a 331 expertos, 301 (91%) completaron la segunda ronda y 295 (98%) completaron la ronda final. Los expertos apoyaron firmemente el uso de una "regla de 10 cm" para describir las localizaciones del cáncer de colon en las flexuras y puntos de referencia anatómicos para otros segmentos. En cuanto a la definición de cáncer rectosigmoideo, expertos de América y Europa alcanzaron un alto consenso en la necesidad de abolir el término "rectosigmoide" como localización del cáncer de colon, a diferencia de los expertos de Asia. La descripción de los cánceres en segmentos que se superponen a alcanzó un consenso del 64%.LIMITACIONES:Las decisiones subjetivas se basan en la experiencia clínica individual de cada experto.CONCLUSIONES:Esta encuesta Delphi, el primer estudio de consenso realizado a nivel internacional, alcanzó un notable nivel de consenso entre un panel de expertos globales. Todavía existe ambigüedad en cuanto a las lesiones superpuestas. (Traducción-Dr. Jorge Silva Velazco ).
Keywords: klinické rozhodování; delfská metoda; průzkumy a dotazníky; Surveys and Questionnaires; Colonic Neoplasms; konsensus; Consensus; Humans; Clinical Decision-Making; lidé; nádory tračníku; Delphi Technique